Enhanced precipitation responses over the Tibetan Plateau following future Tambora-size volcanic eruption - Xin-Jun Gan; Lin-Shan Yang; Meng Zuo; Fei Liu; Chao-Chao Gao (Advances in Climate Change Research)
Hydroclimate over the Tibetan Plateau (TP) notably influences the eco-environment of the Northern Hemisphere. Given its high elevation and complex topography, the climate in the TP shows a high sensitivity to anthropogenic warming and volcanic-induced cooling. The mechanism by which a future volcanic or similar radiative perturbation affects precipitation in the TP under an anthropogenic warming climate must be addressed not only to enable regional adaptation but deepen our understanding of how a climate system evolves under such a dual force. Here, based on the Community Earth System Model version 1.2 and ensemble simulations under pre-industrial and RCP8.5 scenarios, we showed that a Tambora-sized volcanic perturbation led to severe rainfall reduction over the south TP in the following summer (June–August). Evaporation response accounted for a minor and relatively constant share of precipitation reduction following the Clausius–Clapeyron scaling, whereas dynamic processes triggered an El Niño-like response in the eastern equatorial Pacific, which suppressed the Walker and Hadley circulation and contributed to drying anomalies. Global warming renders the post-Tambora hydroclimate responses with 30% higher severity as a result of the increased climatological moisture content and intensified El Niño response, which enhanced hydroclimate sensitivity and attenuated monsoon circulation. The results illustrate the amplification effect of global warming on the plateau's hydroclimate responses to external forcings, which may add another layer of uncertainty on climate adaptation in this already complex region.